Nostalgia, Co-creation, and Practice of Design - Renu Zunjarwad (Cultural Syndrome, 2020)
The study proposes that the research design integrating co-creation, interviews, and visual analysis can effectively operationalize a difficult concept of gastronomic nostalgia surrounding ethnic food artifacts. I employed an example of Mumbai’s street foods to examine consumption, production, and distribution practices and compared the cities of Mumbai, India, and Phoenix, United States. Rigorous qualitative analysis of the data gathered from fourteen Indian immigrants in Phoenix suggested that consumption declined when street foods’ core identity shifted in Phoenix. I discovered that the differences in having street foods in sit-down settings or the lack of a public street food culture might never be bridged in Phoenix. However, specific production and distribution strategies rooted in nostalgic memories from Mumbai may boost consumption.